2020
DOI: 10.1093/toxsci/kfaa065
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Environmental Chemicals on the Gut Microbiome

Abstract: Since the surge of microbiome research in the last decade, many studies have provided insight into the causes and consequences of changes in the gut microbiota. Among the multiple factors involved in regulating the microbiome, exogenous factors such as diet and environmental chemicals have been shown to alter the gut microbiome significantly. Although diet substantially contributes to changes in the gut microbiome, environmental chemicals are major contaminants in our food and are often overlooked. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(67 citation statements)
references
References 152 publications
1
54
0
1
Order By: Relevance
“…It is now increasingly recognized that these commensal microbiota also contribute to the host immune defense, for example, by providing resistance against invading pathogens and by training and stimulation of the host immune system, as reviewed by [ 73 , 115 , 116 ]. Owing to these critical functions provided by intestinal microbiota, their disruption (dysbiosis) by, for example, a dietary change or a chemical exposure may adversely affect the health of the host [ 117 , 118 , 119 ] and in humans is associated to numerous diseases including obesity, inflammatory bowel disease, and diabetes [ 120 ]. Given the central role that microbiota play in host immunity and host health, there is a need to incorporate commensal microbiota in the health risk assessment of NP applications, both from a biomedical standpoint, and in the context of occupational, consumptive, or inadvertent NP exposure [ 121 ].…”
Section: The Long-term Effects Of Np Exposurementioning
confidence: 99%
“…It is now increasingly recognized that these commensal microbiota also contribute to the host immune defense, for example, by providing resistance against invading pathogens and by training and stimulation of the host immune system, as reviewed by [ 73 , 115 , 116 ]. Owing to these critical functions provided by intestinal microbiota, their disruption (dysbiosis) by, for example, a dietary change or a chemical exposure may adversely affect the health of the host [ 117 , 118 , 119 ] and in humans is associated to numerous diseases including obesity, inflammatory bowel disease, and diabetes [ 120 ]. Given the central role that microbiota play in host immunity and host health, there is a need to incorporate commensal microbiota in the health risk assessment of NP applications, both from a biomedical standpoint, and in the context of occupational, consumptive, or inadvertent NP exposure [ 121 ].…”
Section: The Long-term Effects Of Np Exposurementioning
confidence: 99%
“…On the other hand, Western and poor diets have showed an “antibiotic effect” on GM, thanks to lack of fibers, food additives, plastics residues, etc. [ 181 , 182 ], and for this reason, we are observing a disappearance of good microbial species [ 183 ], which, in turn, causes modern diseases.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Environmental chemicals strongly influence microbiota communities with implications to human health ( 8 , 36 ). In a study of the impact of confined swine farm environments on gut microbiome and resistome of veterinary students, it has been found that farm exposure shapes the gut microbiome of these students, with enrichment of potentially pathogenic taxa and antimicrobial resistance genes ( 37 ).…”
Section: Microbiota Interactions With Enviromental Chemicalsmentioning
confidence: 99%
“…The interactions of xenobiotic and host active substances with gut microbiota play key roles in human health, diseases and physiological responsiveness to various cues and treatments ( 1–3 ). Broad variety of xenobiotics such as dietary components ( 4 ), pharmaceuticals ( 2 , 5 , 6 ), herbal products ( 7 ) and environmental chemicals ( 8 , 9 ) are modified by microbiota with altered bioavailabilities, bioactivities and toxic effects in the host. Some of these xenobiotics can also alter microbiota to affect their functions and communications with the host ( 8 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation